Bionomics of Callosobruchus analis (F.) in ten common food legumes. (September 2022) - Mannava, Naveen; Bandi, Sanjay M.; Chandra, Anup; Kumar, Vaibhav; Aidbhavi, Revanasidda; Singh, Bansa; Jambhulkar, Prashant P.
Abstract: Range of edible legumes suffer huge post-harvest deterioration due to infestation by Callosobruchus spp. (Coleoptera: Chrysomelidae). Among the bruchid species, despite wider distribution in India and its destructive potential, Callosobruchus analis (F.) has been largely overlooked. Hence, we report comparative bionomics of C. analis, influence of seed traits and seed losses in ten commonly cultivated food legumes namely, mungbean, urdbean, chickpea- desi, chickpea- kabuli, cowpea, field pea, pigeonpea, rajmash, moth bean and lentil. Oviposition behaviour, developmental rate of insect and seed losses varied significantly under the influence of seed physico-chemical traits under free-choice and no-choice conditions. Cowpea, pigeonpea and rajmash harboured higher number of eggs when choice for legume was offered, however, none of the tested legume was completely avoided for egg laying. The survivability was found negligible on rajmash and field pea. Developmental time was 1.3–1.5 times longer on urdbean (45.97 days) in comparison to other legumes, indicating the role of antibiosis factors. More progenies were produced on pigeonpea, cowpea, moth bean, chickpea- desi and mungbean leading to high seed losses. Seed properties namely, seed surface area, hardness, seed coat thickness, 100-seed weight, seed moisture and phenol contents significantly influenced oviposition behaviour and growth of the insects. Further studies are needed to elucidate exact mode of action of seed traits and their interaction on the insect bionomics. The legumes those suffered considerable seed losses by C. analis warrant adequate preventative measures to avoid cross-infestation under common storage conditions and reduce post-harvest deterioration. Highlights: Comparative bionomics of Callosobruchus analis (F.) and seed losses were reported in ten commonly cultivated food legumes. The oviposition behaviour and developmental rate of C. analis was influenced by physico-chemical traits of the legume seeds. Cowpea, pigeonpea and rajmash reported maximum oviposition. The bruchid produced higher progenies on pigeonpea, cowpea, moth bean, chickpea- desi and mungbean. Survivability of the bruchid was found negligible on rajmash and field pea.